Differential expression of endocannabinoid system in normal and preeclamptic placentas: effects on nitric oxide synthesis. - Aban, Cyntia Estefania (2013)
Anandamide (AEA) is a lipid mediator that participates in the regulation of several reproductive functions. This study investigated the endocannabinoid system in normal (NP) and preeclamptic (PE) placentas, and analyzed the potential functional role of AEA in the regulation of nitric oxide synthesis. The protein expression and localization of NAPE-PLD, FAAH and CB1 receptor were analyzed in normal and preeclamptic pregnancies using immunoblotting and immunohistochemistry. NAPE-PLD expression was shown to be significantly higher (p < 0.05) in PE tissues than in NP. In contrast, a decrease in FAAH protein (p < 0.001) was detected in placentas collected from women with preeclampsia. Both enzymes were mainly located in the syncytiotrophoblasts from normal and preeclamptic tissues. No differences were seen in CB1 receptor from both groups of placental villous. Exogenous and endogenous AEA significantly increased NOS activity. Although pre-incubation with AM251 (CB1 antagonist) had no effect, co-incubation with both AEA and AM251 diminished NOS activity from normal term placentas. We observed increased NOS activity in placental villous from women with preeclampsia compared with normotensive pregnant women. Furthermore, NOS activity from preeclamptic tissues was diminished by co-treatment with AM251, illustrating that the NO levels could be modulated by AEA.These data suggest that AEA may be one of the factors involved in the regulation of NOS activity in normal and preeclamptic placental villous. Interestingly, the differential expression of NAPE-PLD and FAAH suggests that AEA could play an important role in the pathophysiology of PE.